REFRESHING DAN PELATIHAN KADER SEBAGAI UPAYA PENINGKATAN KOMPETENSI KADER DI KALURAHAN UMBULMARTANI KAPANEWON NGEMPLAK KABUPATEN SLEMAN - Setyaningsih, Dewi; Yuliani, Istri Yuliani; Nugroho, Setyo Mahanani; Nurtyas, Maratusholikhah (Universitas Respati Yogyakarta, 2021)
Background: One of the efforts to accelerate the reduction of maternal and infant mortality rates is carried out in the Posyandu program. Cadres have a major contribution in reducing maternal and infant mortality. Improving the knowledge and skills of cadres through training is needed, so that cadres are able to manage Posyandu activities according to their abilities. The problemÂ is that not all cadres get knowledge routinely about posyandu, the aims and objectives of administering, the posyandu targets in PUS, WUS, mothers and children. Especially in the pandemic posyandu activities require some adjustments and additional knowledge, especially regarding Health protocols.Objective: To increase the knowledge of cadres in implementing posyandu in the form of counseling and discussions about updating the roles and duties of posyandu cadres in the New Normal Era.Methods: The activities carried out were refreshing cadres with counseling activities and discussions on updating the roles and duties of posyandu cadres in the New Normal Era. Counseling and discussion activities during this pandemic were carried out online in the form of video calls. Participants were provided with learning materials so they could study independently. Knowledge measurement was carried out by giving pre and post tests.Results: There was an increase in cadre knowledge before and after training. The results of the post test showed that the lowest score was 7 and the highest score was 9, with an average score of 8 (64.29%).Conclusion: Refreshing for posyandu cadres are very important to carry out in an effort to increase knowledge and skills for posyandu cadres, so that posyandu implementation can be carried out properly, especially during the pandemic.